Alternative communication on the threshold of the third millennium - Roncagliolo, Rafael (1998)
The proposal of a world of all voices, which AMARC launches, configures challenge and bets stubbornly. Against all odds. Not just the many times of the McBride Commission Report. Let's all now. Those of each nation, those of each culture, those of each blood, those of all men and women.